Comparison of GIP and GLP-1 promoter-mediated insulin expression in Gut K and L-cells for the potential treatment of diabetes mellitus - Rasouli, Mina (2012)
Diabetes mellitus is characterized by abnormally high blood glucose levels, which causes serious complications. It is hypothesized that gut K and L-cells could make potential candidates for diabetes gene therapy manipulation. The project was carried out to determine and compare the quality and quantity of the human insulin expressed in both mice K and L-cells in vitro and in vivo which have been transfected with human insulin gene construct with GIP and GLP-1 promoters. These cells do not naturally produce insulin but respond to glucose and other nutrients in the gut by secreting GIP (glucose-dependent insulinotropic polypeptide) and GLP-1 (glucagon-like peptide-1) which then stimulate beta cells of pancreas to produce insulin. For this purpose, two plasmids containing neomycin with GIP or GLP-1 were constructed to isolate pure surrogate models for in vitro studies. The next two plasmids containing insulin with GIP or GLP-1 were constructed in order to study efficiency and efficacy of insulin expression in vitro and in vivo and the last two plasmids containing GFP with GIP or GLP-1 were constructed to study delivery efficiency of gene vehicle in vivo. We also studied different nutrients stimulus effects and time expression of the insulin secretion in both the K and L cells. Finally, the insulin expression efficacy of the reconstructed plasmids with GIP and GLP-1 promoters in lowering the glucose levels was compared in diabetes animal model. To study these hypotheses, neomycin, insulin and GFP genes were inserted downstream of the promoters in 6 different recombinant constructs. QRT- PCR was used to authenticate the purity of the isolated K and L-cell lines. Isolated K and L-cell lines were then transfected by recombinant insulin constructs. RT-PCR, immunocytostaining and Western blotting were used to analyze qualification of mature insulin while QRT- PCR and ELISA were employed to quantify the secreted insulin from both cell-lines. Glucose and meat hydrolysate (MH) were used to study different stimulant effects on insulin expression in both cell lines. The secretion of insulin was investigated for 180 min in 6 different time points. For in vivo studies, chitosan was employed to transfer the recombinant insulin constructs into the target cells orally. The ability of chitosan to deliver the constructs was investigated using immunohistostaining on the intestine of the mice. The effect of secreted insulin on lowering the glucose levels in STZ-induced diabetic mice was investigated by blood glucose testing in two weeks duration. QRT-PCR results proved that the isolated cells were pure K and L-cell. The Western blotting and immunocytostaining results of insulin secretion studies revealed that both cells were able to produce mature and active insulin. Statistical analysis revealed that the difference between insulin expressions from K and L-cells in relation to the glucose and MH stimulations were not significant. The immunohistostaining results showed that chitosan was an efficient gene vehicle to transfect the intestinal cells. In addition, RT-PCT and ELISA confirmed that pure human insulin was expressed in vivo. Blood glucose testing results showed that the treatment with the recombinant insulin gene significantly reduced glucose levels in diabetic mice. As a conclusion, recombinant neomycin constructs successfully produced pure K and L-cells. Recombinant insulin constructs comparably efficiently produced mature insulin protein in K and L-cells in vitro and in vivo. The response of K and L-cells to induction of both stimulators was mostly comparable. However, meat hydrolysate is found to be a more potent insulin secretion agonist for both cells than glucose. In addition, our in vivo results provided successful preliminary data that proved the analogous ability of both GIP and GLP-1 insulin constructs in lowering blood glucose levels of the diabetic mice.